(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The Author discusses the Constitutional Court’s judgment no. 96 of 2015 on the constitutional legitimacy for fertile couples to make use of medically-assisted procreation techniques prior to a pre-implantation genetic diagnosis. After a brief analysis of its content, the Author investigates the Constitutional Court’s decision from the angle of its relationship with the European Court of Human Rights’ ruling in the Costa & Pavan v. Italy case. The Author then goes on by addressing the challenges of the mechanisms of interplay between the two Courts, by questioning, on the one hand, the Constitutional Court’s refusal to make use of Article 117, § 1, of the Italian Constitution and, on the other, by highlighting the coherence of the arguments between the two judgments.